2010
DOI: 10.1021/jp108734u
|View full text |Cite
|
Sign up to set email alerts
|

Localized and Dispersive Electronic States at Ordered FePc and CoPc Chains on Au(110)

Abstract: Iron and cobalt phthalocyanines assemble on the Au(110) surface lying parallel to the surface, as deduced by near-edge X-ray absorption fine structure (NEXAFS) taken with linearly polarized radiation at the C and N K edges. The molecular chains, firmly anchored to the underlying metal surface, arrange into long-range ordered rows with a (5 × 3) symmetry along the [001] azimuthal direction at completion of the first single layer. The interaction process is mainly determined by the d orbitals associated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
136
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(156 citation statements)
references
References 49 publications
(136 reference statements)
20
136
0
Order By: Relevance
“…Still several UPS and ARPES studies have reported on the formation of interacting and hybrid states at the organic/noble-metal interface within the substrate d-band region. 12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] In these studies intense and sharp photoemission features were found upon the adsorption of large (M-Pc, pentacene) and smaller (anthracene, small thiols, adenine) organic molecules. Ab initio calculations and polarization dependent and angular-resolved measurements were also reported generally highlighting the interface character of the photoemission features.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Still several UPS and ARPES studies have reported on the formation of interacting and hybrid states at the organic/noble-metal interface within the substrate d-band region. 12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] In these studies intense and sharp photoemission features were found upon the adsorption of large (M-Pc, pentacene) and smaller (anthracene, small thiols, adenine) organic molecules. Ab initio calculations and polarization dependent and angular-resolved measurements were also reported generally highlighting the interface character of the photoemission features.…”
Section: Discussionmentioning
confidence: 91%
“…14,15 Despite this difficulty several studies reported on the formation of hybrid molecule-substrate interface states within the single-crystal substrates d-band BE region. 12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] The present paper focuses on the substrate contribution in the EDC of the adsorbed system and it highlights the importance of the interface scattering when interpreting the EDC of a thin layer of large, π -conjugated organic molecules on noble-metal single-crystal substrates. As will be shown in the following, the adsorption promotes the measurements of EDCs in photoemission that are reminiscent of the metal three-dimensional (3D)-integrated DOS, i.e., EDCs that mimic polycrystalline metal surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…1 provides quantitative information about the orientation of the deposited films. 1,9,12,13,18,25 The N 1s edge of transition metal phthalocyanines is influenced by the nature of the central metal atom, 42 but we do not focus on these effects here as they do not strongly affect the use of the N 1s edge as a probe of molecular orientation. Well-ordered films were obtained on Si wafers covered with the native oxide, a widely used substrate.…”
Section: A Sample Preparation and Characterizationmentioning
confidence: 99%
“…5 There is a substantial amount of literature on the characteristic multiplet structure of the metal 2p-to-3d transitions in such molecules. [6][7][8][9][10][11][12][13][14][15] For Mn see Refs. 16 Here we focus on the crystal field generated by the negatively charged N atoms surrounding the central metal ion of porphyrins and phthalocyanines.…”
Section: Introductionmentioning
confidence: 99%
“…The spectra for the thickest layers (1.6 and 2.1 nm) agree very well with CoPc film spectra reported in literature. 16,19,24,25,27 The shape can be described by multiplet structures. At lower CoPc film thickness on both substrates, a new peak at lower binding energy (778.0 eV) appears and dominates the spectrum of the CoPc layer with smallest thickness (0.2 nm).…”
mentioning
confidence: 99%